Patterns of left ventricular recovery in patients with heart failure with mid-range ejection fraction. (14th October 2021) - Chen, H.H.L; Lee, C; Dhamoon, K; Bhat, A; Gan, G.C.H; Tan, T.C
Abstract: Background: Heart failure with mid-range ejection fraction (HFmEF) represents a new classification of heart failure with intermediate clinical characteristics to those with HF with reduced ejection fraction (HFrEF) and HF with preserved ejection fraction (HFpEF). A proportion of HFmEF is attributed to atrio-ventricular dyssynchrony from atrial fibrillation (AF) as opposed to a primary cardiomyopathy with intrinsic cardiac myocyte dysfunction. Purpose: We aim to compare the rate of left ventricular ejection fraction (LVEF) recovery in those with AF-mediated cardiomyopathy compared to those with primary myocyte dysfunction. Methods: Consecutive patients with stable non-ischaemic cardiomyopathy with LVEF 40–49% on transthoracic echocardiography (TTE) were recruited from our institution's heart failure clinic and followed for 18 months. Patients with ischaemic, valvular or congenital heart disease, incomplete follow-up or poor quality TTE images were excluded. Eligible patients were separated into two groups: AF-mediated (n=44); and primary myocyte dysfunction (n=116). Results: A total of 160 patients (62.1±16.4 years, 62% men) were included. There was no significant difference in age (p=0.06) and gender (p=0.59). Comorbid AF was higher in those with AF-mediated HFmEF (100 vs 28.4%; p<0.01), otherwise no significant differences in clinical history was found between groups. AF-mediated HFmEF had lower rates of cardiac-specific beta-blocker use (15.9 vs 47.4%; p<0.01). Baseline TTE showed similar LVEF and LV global longitudinal strain. On log-rank analysis there was no significant difference in all-cause death (p=0.75), or HF-related hospitalisation (p=0.14), however, higher rates of LVEF recovery were observed in the AF-mediated HFmEF group (p<0.01). See figure 1. Conclusion: There were higher rates of LVEF recovery in those with AF-mediated HFmEF compared to those with a primary myocardial disorder despite lower rates of cardiac-specific beta-blocker use. This did not translate to improvements in intermediate-term survival or HF related hospitalisation. These findings provide insight into the natural history of the disorder and its clinical phenotype. Funding Acknowledgement: Type of funding sources: None.